Black holes in anti-de Sitter (AdS) spacetime - Villegas, Fulgencio (2022)
The space-time metric AdS will be determined and based on it the cosmological constant will be calculated as a function of the radius of the space AdS, using this cosmological constant the Einstein equations will be solved in order to find a metric based on from the radial coordinate of the event horizon, then some thermodynamic properties of black holes in spacetime AdS such as temperature, area and entropy will be calculated.